Four Junction Traffic Light Controller using PLC (S7-200) - Nyan Phyo Aung; Mo Mo Myint Wai; Lwin Lwin Htay (Journal La Multiapp, 2020)
Advance of a road traffic light control system using Programmable Logic Controller is the principal of the system. This system can be divided into two parts which are hardware and software. The hardware part for this system is a model of four -way junction of a traffic light. The Red, Yellow and Green are installed at each lane to represent as a traffic light signal indicator. This switches and lamps are linked to PLC. The PLC receives signal which is coming from the inputs (sensor and switch) and drives the units (lamps or relays). In the system, Siemens s7-200 PLC is used as the main controller of the traffic light system. The Step7 Micro Win software can be developed the ladder logic diagram which can control the traffic light for proposed system. So, the traffic light system can be successfully controlled by PLC.